Narativna struktura Kovačičevega romana Deček in smrt - Cafuta, Maja (Jezik in slovstvo, 2011)
The discussion focuses on the narrative structure of the novel Deček in smrt (1968) by Lojze Kovačič. Specifically, we attempt to determine which narrative methods and categories are used in the selected prose work, that is, how and with which techniques the subjective inner experience of the literary figure is presented. In so doing, we refer to the discussion of D. Cohn, who mentions various narrative methods for presenting the inner experience of the literary figure in the first person and third person context. In the analysis,we also take into account theoretical concepts of the linguistic representation of speech and thought from the perspective of literary style (Short, Leech, Semino, Fludernik), and thus delineate the narrative and experiential I in the story, as well as determining and emphasising the signals with which the two interweave and reflect themselves in the text.
Keywords: Kovačič, Lojze, 1928-2004; Deček in smrt; Slovene literature; slovenska književnost; romani; Kovačič, Lojze: Deček in smrt; naratologija; narratology; pripovedni postopki; prvoosebni pripovedovalec